2014
DOI: 10.1103/physrevlett.112.095001
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Neutron Production from a Novel Configuration of Deuterium Gas-PuffZ-Pinch

Abstract: A novel configuration of a deuterium z pinch has been used to generate fusion neutrons. Injecting an outer hollow cylindrical plasma shell around an inner deuterium gas puff, neutron yields from DD reactions reached Y(n)=(2.9 ± 0.3) × 10(12) at 700 ns implosion time and 2.7 MA current. Such a neutron yield means a tenfold increase in comparison with previous deuterium gas puff experiments at the same current generator. The increase of beam-target yields was obtained by a larger amount of current assembled on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 20 publications
0
25
0
3
Order By: Relevance
“…It is worth noting that recent experimental results from deuterium gas puffs suggested that magnetization effects may be present for neutrons with energies greater than 10 MeV. 45 …”
Section: Magnetization As a Cause Of Isotropic Beam-target Spectramentioning
confidence: 99%
“…It is worth noting that recent experimental results from deuterium gas puffs suggested that magnetization effects may be present for neutrons with energies greater than 10 MeV. 45 …”
Section: Magnetization As a Cause Of Isotropic Beam-target Spectramentioning
confidence: 99%
“…В последующих экспериментах по исследованию дейтериевых плазмен-ных фокусов при уровне тока порядка 1 МА были за-регистрированы электронные пучки, жесткое рентгенов-ское излучение и " надтепловые" дейтроны с энергией до 8 MeV [10]. Еще более энергичные дейтроны с энергией в несколько десятков MeV были зарегистрированы в экспериментах по сжатию дейтериевых лайнеров [11] при уровне тока 2.7 МА. Для объяснения генерации высокоэнергичных ионов и жесткого рентгеновского излучения в работе [12] был предложен так называе-мый " мишенный" механизм.…”
unclassified
“…При a = 10, L hs = 10 −3 cm и I = 10 · I A τ ≈ 10 −3 ns. То есть кулонов-ский взрыв микропинча происходит практически мгно-венно после достижения в микропинче условия (11). Оценка времени взрыва, безусловно, занижена, так как в ней не учитываются не только токи смещения, но и приход тепловых электронов в область " горячей точки".…”
unclassified
See 1 more Smart Citation
“…Since there is need for a repetitive neutron sources, the deuterium Z-pinch became a more remarkable subject of research than in the past, when it mainly served as an effective source of X-rays [2]. Apart from the greatest Z-pinch device -the Z machine with the neutron yield 4 × 10 13 [3], there are several smaller but still quite effective deuterium gas-puff devices producing relatively large amounts of fast neutrons. One of them is the GIT-12 device, situated in Tomsk, Russia, which is able to produce more than 10 12 neutrons per shot.…”
Section: Introductionmentioning
confidence: 99%